Metals and Alloys : Industrial Applications - Benvenuto, Mark Anthony (De Gruyter Textbook, 2016)
Metals and Alloys continues the series of graduate textbooks on Industrial Chemistry by Mark A. Benvenuto. It shows the essential industrial applications, processes and chemistry background for the extraction of metals, as well as the production and applications of alloys. The book discusses how large scale and minor processes affect every-day life, challenges in prevention and removal of waste by-products and illustrates selected chemical processes for which efforts have been made to improve and "green" industrial production of metals and alloys. Sources for metals are sorted by metal and alloy and backed by basic chemical background information and process set up. Overviews on worldwide ore distribution, refined metal and alloy production numbers are another focus of the book. Discusses sources, key processes and applications. Connects what students learn in class to real, large-scale metals chemistry that makes modern life possible. Intended for students, graduate students and beginners in the fiield of Chemistry, Chemical Process Engineering, Chemical Engineering and Materials Science. Visit degruyter.com for more information on books by Mark A. Benvenuto: Industrial Chemistry (2013), Industrial Chemistry: For Advanced Students (2015) and Industrial Inorganic Chemistry (2015). About the Author: Mark Anthony Benvenuto A Fellow of the American Chemical Society, he received his PhD in inorganic chemistry from the University of Virginia. After a post-doctoral fellowship at the Pennsylvania State University, he joined the University of Detroit Mercy, where he is now the Department Chairman and teaches an industrial chemistry course.